Prospects for using combined heat and power plants and boiler houses to balance the integrated energy system of Ukraine - Khodakivskyi, Vitalii; Karpenko, Dmytro (Technologies and Engineering, 2025)
The study analysed the current state of Ukraine’s energy system, focusing on the shortage of manoeuvring capacities, large emissions of harmful substances into the atmosphere, and low energy efficiency of the key technological processes of existing generation facilities. These shortcomings also apply to heat energy producers, namely combined heat and power stations and industrial and municipal boiler houses. The existing energy system of Ukraine includes both types of producers, with a predominant type of energy (electricity or heat). The purpose of this study was to assess the prospects for introducing modern technologies to ensure the sustainability of electricity and heat production systems. The analytical methods used were those suitable for comparing gas turbine and combined cycle plants, as well as electricity and heat storage systems. The study reviewed various technologies that increase the manoeuvrability of systems for the production of these types of energy and reduce the generation of harmful substances by avoiding endothermic reactions in the combustion of solid, liquid, and gaseous fuels. Changes in the ratio of capacities of the main generating facilities built in the 1960s, deterioration of technological equipment, which has exhausted its technological life by 80-90%, indicate a lack of manoeuvring capacities and its aggravation as a result of destruction and damage caused by military aggression. The need to modernise coal-fired thermal power plants using modern combustion technologies in an environment enriched with oxygen (up to 30-40%) of atmospheric air was also emphasised. To improve the manoeuvrability of coal-fired units, it is necessary to bring their capacity to the level of 800-1000 MW, and to significantly reduce emissions of harmful substances, it is necessary to combine steam, gas, and combined cycle generation. The study explored the prospects for the development of highly manoeuvrable capacities through the reconstruction of existing combined heat and power plants and the conversion of municipal and industrial boilers into mini-cogeneration plants for their integration into the European energy market. The results can form the basis for the development of a state energy policy that will help increase the resilience and efficiency of Ukraine’s energy system, reduce its dependence on electricity imports, meet environmental standards at both the national and European levels, and guarantee the country’s energy security.